Mediation of Potato–Potato Cyst Nematode, G. rostochiensis Interaction by Specific Root Exudate Compounds - Ochola, Juliet; Cortada, Laura; Ng’ang’a, Margaret; Hassanali, Ahmed; Coyne, Danny; Torto, Baldwyn (Frontiers in Plant Science, 2020)
Potato (Solanum tuberosum) is a widely consumed staple food crop worldwide whose production is threatened by potato cyst nematodes (PCN). To infect a host, PCN eggs first need to be stimulated to hatch by chemical components in the host root exudates, yet it remains unknown how most root exudate components influence PCN behaviour. Here, we evaluated the influence of eight compounds identified by LC-QqQ-MS in the root exudate of potato on the hatching response of the PCN, Globodera rostochiensis at varying doses. The eight compounds included the amino acids tyrosine, tryptophan and phenylalanine; phytohormones zeatin and methyl dihydrojasmonate; steroidal glycoalkaloids α-solanine and α-chaconine and the steroidal alkaloid solanidine. We additionally tested two other Solanaceae steroidal alkaloids, solasodine and tomatidine, previously identified in the root exudates of tomato, an alternative host for PCN. In dose-response assays with the individual compounds, the known PCN hatching factors α-chaconine and α-solanine stimulated the highest number of eggs to hatch, ~42% and ~36% respectively, whereas the steroidal alkaloids (aglycones), solanidine and solasodine were intermediate, 15% each, with tomatidine eliciting the lowest hatching response (<0%). However, ~60% of the hatched juveniles failed to emerge from the cyst, which was compound- and concentration-dependent. The amino acids and phytohormones, however, were generally non-stimulatory. The use of steroidal glycoalkaloids and their aglycones in the suicidal hatching of PCN offers promise as an environmentally sustainable approach to manage this pest.